Differentiating between signs of intra‐articular joint bleeding and chronic arthropathy in haemophilia: a narrative review of the literature. (9th April 2015) - Timmer, M. A.; Pisters, M. F.; de Kleijn, P.; de Bie, R. A.; Fischer, K.; Schutgens, R. E.
<x xml:space="preserve">Abstract</x> Introduction Elderly patients with haemophilia (PWH) suffer from both haemarthrosis and haemophilic arthropathy (HA). Diagnosis of haemarthrosis in PWH is currently based on clinical presentation. No diagnostic protocols or validated criteria are available to identify haemarthrosis or to differentiate haemarthrosis from HA. Aim The aim of this study is to identify symptoms and signs that can be used to differentiate haemarthrosis from HA. Methods A narrative literature review was performed on symptoms associated with haemarthrosis and symptoms associated with HA. Additionally, literature on the diagnosis of haemarthrosis in patients without haemophilia, imaging techniques and biomarkers was searched. Results This review shows that there is no consensus about the symptoms associated with haemarthrosis and that there is limited literature about the symptoms associated with HA. Additionally, symptoms associated with haemarthrosis partly overlap with symptoms of HA, particularly those symptoms associated with flare‐ups of HA. Due to the overlap in symptoms differentiating between these conditions is complex. Furthermore, differentiating based on imaging techniques or biomarkers causes practical difficulties. Conclusion Despite the overlap in symptoms, differentiating between joint bleeds and flare‐ups of HA based on clinical presentation still seems the most convenient and practical solution. Further research is necessary to identify specific symptoms that can be used to differentiate between the two conditions.